Pengembangan Lms Moodle Berbasis Project Based Learning Untuk Meningkatkan Kompetensi Kognitif Pada Elemen Pemrograman Web Siswa Kelas Xi Rpl Smk Negeri 4 Bojonegoro - Salvia Nabillah Syifa; Ersha Aisyah Elfaiz (CV. SINAR HOWUHOWU, 2026)
The implementation of digital learning media for the Web Programming element at SMK Negeri 4 Bojonegoro remains significantly constrained, leading to a high reliance on conventional teaching methods and a lack of a specialized Learning Management System (LMS) that supports project-based learning. This research aims to develop a Project-Based Learning (PjBL)-based Moodle LMS called DigiLearn and analyze its effectiveness in improving the cognitive competence of students. Using a Research and Development (R&D) approach with the ADDIE model, this study employed a Nonequivalent Control Group Design. The study involved two classes of eleventh-grade Software Engineering (RPL) students, split into an experimental group (XI RPL 1) and a control group (XI RPL 2), each consisting of 34 students. The developed LMS was integrated with the Monitoring Kanban Board plugin to help students track their project milestones through To Do, Doing, and Done categories. Data collection was conducted via expert validation and pretest-posttest instruments, subsequently analyzed using feasibility percentages, N-Gain tests, and Independent Samples t-Tests. The validation results demonstrated that the LMS is highly feasible for implementation. The N-Gain analysis revealed that the experimental group achieved a score of 0.712 (high category), significantly outperforming the control group's score of 0.381 (moderate category). Furthermore, the Independent Samples t-Test confirmed a statistically significant difference in cognitive competence between the two groups. It is concluded that the PjBL-based Moodle LMS is highly effective in enhancing students' cognitive competence within the Web Programming element.